ACADEMIA DOS REBELDES: MODERNISMO À MODA BAIANA - Soares, Angelo Barroso Costa (2006)
The dissertation entitled The Rebels´ Academy: modernism in the Bahian way analyses the constitution and the intellectual production of the Rebels´ Academy, an association that emerged in Bahia at the beginning of the 20th century with the aim of producing modern literature. Thus, this study looks at modernism in Brazil in order to present the historical and cultural context in which an innovative proposal was put forward in different Brazilian states. Subsequently, this study examines the peculiarities of the so-called Bahian modernism , based upon the composition and proposition of the Rebels´ Academy, whose members were Bahian writers and intellectuals who started working for local newspapers, aspiring to an intellectual career. In their ideological and aesthetic project, this group opted for the high valuation on the local popular culture, particularly, the African and Afro-Bahian culture, which had been marginalized during the colonization process of Brazil. Additionally, with a view to understanding the signs of innovation shown by the Rebels´ Academy , this study focuses on the periodicals produced by this group, the Meridiano and O Momento magazines, in which the proposals for modern literature, in a Bahian version, are more firmly suggested